Muscle satellite cell heterogeneity and self-renewal - Motohashi, Norio; Asakura, Atsushi (Frontiers in Cell and Developmental Biology, 2014)
Adult skeletal muscle possesses extraordinary regeneration capacities. After muscle injury or exercise, large numbers of newly formed muscle fibers are generated within a week as a result of expansion and differentiation of a self-renewing pool of muscle stem cells termed muscle satellite cells. Normally, satellite cells are mitotically quiescent and reside beneath the basal lamina of muscle fibers. Upon regeneration, satellite cells are activated, and give rise to daughter myogenic precursor cells. After several rounds of proliferation, these myogenic precursor cells contribute to the formation of new muscle fibers. During cell division, a minor population of myogenic precursor cells returns to quiescent satellite cells as a self-renewal process. Currently, accumulating evidence has revealed the essential roles of satellite cells in muscle regeneration and the regulatory mechanisms, while it still remains to be elucidated how satellite cell self-renewal is molecularly regulated and how satellite cells are important in aging and diseased muscle. The number of satellite cells is decreased due to the changing niche during ageing, resulting in attenuation of muscle regeneration capacity. Additionally, in Duchenne muscular dystrophy (DMD) patients, the loss of satellite cell regenerative capacity and decreased satellite cell number due to continuous needs for satellite cells lead to progressive muscle weakness with chronic degeneration. Thus, it is necessary to replenish muscle satellite cells continuously. This review outlines recent findings regarding satellite cell heterogeneity, asymmetric division and molecular mechanisms in satellite cell self-renewal which is crucial for maintenance of satellite cells as a muscle stem cell pool throughout life. In addition, we discuss roles in the stem cell niche for satellite cell maintenance, as well as related cell therapies for approaching treatment of DMD.